A case of stifle osteochondrosis treated by osteochondral autogenous grafting - Palierne, S.; Bilmont, A.; Raymond-Letron, I.; Autefage, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
Objective: To describe the one-month morphological appearance of autogenous osteochondral grafting in a dog with stifle osteochondrosis.Method: Osteochondral autografting was performed in one stifle of an eight-month-old dog with spontaneously occurring bilateral osteochondrosis.Result: Histopathological analysis performed one month after surgery confirmed partial integration of the grafts and osteochondral survival.Clinical significance: Autogenous osteochondral grafting in stifle osteochondrosis results in acceptable graft survival postoperatively and is worthy of further evaluation.
Keywords: Osteochondrosis; stifle; autogenous osteochondral grafting